(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This systematic review explores the critical role social media plays in shaping consumer behavior in the context of online retail. With the rapid digital transformation and the increasing reliance on e-commerce platforms, consumers are turning to social media for information, validation, and inspiration. Platforms like Instagram, Facebook, YouTube, and Twitter have emerged not only as marketing channels but also as primary sources of consumer decision-making. The review synthesizes data from various empirical studies, focusing on factors such as trust in user-generated content, the influence of social media influencers, demographic patterns, and psychological drivers like brand engagement and social proof. The findings reveal that social media significantly affects brand awareness, product discovery, impulse buying, and purchase decisions. Millennials and Gen Z are the most responsive consumer groups, driven by visuals, peer reviews, and instant accessibility. This paper concludes by highlighting emerging trends, practical implications for marketers, and gaps for future research in understanding digital consumer psychology.